A review of motivations and risk factors of cyberbullying - Lim, Wei Shun (Nanyang Technological University, 2021)
Bullying has been a pervasive problem across the world. With the increasing prevalence of technology in our everyday lives, it has evolved to cyberbullying on online platforms and encompasses many new forms. Cyberbullying has been found to bring about negative effects on both victims and bullies. Even as instances of cyberbullying continue to increase, the numbers gathered are usually an underestimate of actual rates of cyberbullying due to poor measurements and the lack of awareness. Although cyberbullying occurs across various demographics, inconsistencies are common among results found. However, among the various reasons people use to explain why netizens engage in cyberbullying, one major theme that can be identified is that cyberbullies have a motivation to engage in behaviours to cyberbully. To provide a new perspective on cyberbullying, this paper will be examining cyberbullying perpetration motivations, including paralinguistic digital affordances, needs for relatedness and autonomy, revenge, entertainment, power, anonymity, social learning, rational choices, self-control, strain and coping mechanisms. The paper will also look into the risk factors surrounding cyberbullying, such as competencies, prior involvement in bullying, bully-victim roles, attitudes towards bullying, social support, parenting styles and social media usage, to explain discrepancies between demographics in cyberbullying perpetration.